A musical group to improve the quality of life. Background and proposal - Vernia-Carrasco, Ana Mercedes (European Public & Social Innovation Review, 2025)
Introduction: Active music practice can be considered a good tool for improving the quality of life of people with dementia. This paper combines an experience with a brief theoretical review. Objectives: The objectives were to show the experience of a group of older people who have no knowledge of music, but who learn songs from memory and share them in a hospital. Methods: observation and ethnographic methodology, which are part of the qualitative methodology, were combined. This methodology made it possible to observe the participants and at the same time to live with them during the active music sessions. Results: several articles were found that support the use of active music to improve the quality of life, in addition to reducing stress in hospital situations. It was also observed that the hospital experience with the musical group was beneficial for participants, caregivers, and physicians.. Conclusions: Programs that use music to improve the quality of life of people with dementia are useful, although more research is still needed. It is necessary to be able to design specific programs that can be adapted to specific patient profiles. Music is suitable as a non-invasive treatment, and can be combined with pharmacological treatments.